The Criminal Prosecution: Sporting Event or Quest for Truth? A Progress Report - William J. Brennan Jr. (Washington University Law Quarterly, 1990)
The subject of my lecture in 1963 was discovery in criminal cases: whether we should extend to criminal prosecutions the civil pretrial discovery techniques that force the parties to a civil lawsuit to put all their cards on the table before trial, and that tend to reduce the chance that surprise or maneuver-rather than truth-may determine the outcome of the trial. A long tenure on the bench and the indulgence of kind hosts give me the opportunity upon occasion to revisit views expressed in the past, and to see how my suggestions and predictions have fared over the years. That is what I propose to do in this lecture. In my experience, the results of such an exercise must be mixed. The last quarter-century has seen significant advances in many areas of the law, including criminal discovery. But as I said in 1963, "the quest for better justice is a ceaseless quest," and "the single constant of our profession is the need for continuous examination and reexamination of our premises as to what law should do to achieve better justice." Law's evolution is never done, and for every improvement made there is another reform that is overdue. Hence the subtitle I have chosen for this lecture on criminal discovery: A Progress Report.
Keywords: Criminal procedure; Discovery (Law)